SPINK1, PRSS1, CTRC, and CFTR Genotypes Influence Disease Onset and Clinical Outcomes in Chronic Pancreatitis. Issue 11 (November 2018) - Zou, Wen-Bin; Tang, Xin-Ying; Zhou, Dai-Zhan; Qian, Yang-Yang; Hu, Liang-Hao; Yu, Fei-Fei; Yu, Dong; Wu, Hao; Deng, Shun-Jiang; Lin, Jin-Huan; Zhao, An-Jing; Zhao, Zhen-Hua; et al.
Abstract Objectives Rare pathogenic variants in theSPINK1, PRSS1, CTRC, andCFTR genes have been strongly associated with a risk of developing chronic pancreatitis (CP). However, their potential impact on the age of disease onset and clinical outcomes, as well as their potential interactions with environmental risk factors, remain unclear. These issues are addressed here in a large Chinese CP cohort. Methods We performed targeted next-generation sequencing of the four CP-associated genes in 1061 Han Chinese CP patients and 1196 controls. To evaluate gene–environment interactions, the patients were divided into three subgroups, idiopathic CP (ICP;n  = 715), alcoholic CP (ACP;n  = 206), and smoking-associated CP (SCP;n  = 140). The potential impact of rare pathogenic variants on the age of onset of CP and clinical outcomes was evaluated using the Kaplan–Meier model. Results We identified rare pathogenic genotypes involving theSPINK1, PRSS1, CTRC, and/orCFTR genes in 535 (50.42%) CP patients but in only 71 (5.94%) controls (odds ratio = 16.12;P  < 0.001). Mutation-positive patients had significantly earlier median ages at disease onset and at diagnosis of pancreatic stones, diabetes mellitus and steatorrhea than mutation-negative ICP patients. Pathogenic genotypes were present in 57.1, 39.8, and 32.1% of the ICP, ACP, and SCP patients, respectively, and influenced age at disease onset and clinical outcomes in all subgroups. Conclusions We provide evidence that rare pathogenic variants in theSPINK1, PRSS1, CTRC, andCFTR genes significantly influence the age of onset and clinical outcomes of CP. Extensive gene–environment interactions were also identified.